RELATIONSHIP BASIC SANITATION OF THE HOME ENVIRONMENT AND HAND WASHING BEHAVIOR WITH SOAP WITH DIARRHEA (Case Study in Kalikatak Village, Arjasa District, Sumenep Regency) - Era Novita Vita; Imam Thohari; Darjati (Jurnal Hygiene Sanitasi, 2021)
Diarrhea is a disease that is still a public health problem in Indonesia. In Kalikatak Village, the number of diarrhea pain in 2018, 2019, 2020 increased by 146 cases (15.05%), 165 cases (17.01%), 182 cases (18.76%). The purpose of this study is to analyze the relationship of basic sanitation of the home environment and CTPS behavior with the incidence of diarrhea in Kalikatak Village, Arjasa Subdistrict, Sumenep Regency. The research method used is an analytical method with a case control approach. The population in this study is the entire head of the family who live in Kalikatak Village with the number of research samples calculated using the lemeshow formula obtained by 87 people. Case and control sample determination is taken with a proportion of 1 : 1. A total sample of 174 people. Data collection techniques are primary data retrieval through questionnaires and observations by analyzing using Chi-Square test. The results showed that clean water facilities were related (p = 0.001 <0.05), toilets were not related (p = 0.905> 0.05), wastewater disposal facilities were related (p = 0.000 <0.05), facilities waste disposal was correlated (p = 0.000 <0.05), food and beverage sanitation hygiene was not correlated (p = 0.801> 0.05), basic sanitation facilities of the home environment were correlated (p = 0.000 <0.05), and on CTPS behavior of knowledge p = 0.05, attitude there is no relationship (p = 0.405> 0.05), action there is no relationship p = 0.479> 0.05. The community has a role to play in improving basic sanitation facilities for the home environment such as improving the quality of clean water facilities, waste water disposal facilities and waste disposal facilities and the role of puskesmas to provide information about the importance of basic home environment sanitation for health.